Pengaruh Vitamin D terhadap Keparahan dan Mortalitas COVID-19 - Ari Wahyuni; Jundi Fathan Mubina (Medula, 2021)
COVID-19 which caused by SARS-CoV 2 infection has becoming health crisis globally. There is urgent need to identify strategy to reduce the level of severity and mortality of COVID-19. However little is known about protective factors for this infection. This review aim to discuss the possible effect of vitamin D in reducing severity and mortality risk of COVID-19. This literature review use several journal databases, namely PubMed, Google Scholar, and ScienceDirect and analysis was carried out qualitatively. The result obtained 10 literature two of which were randomized controlled trials. The result of retrospective analysis shows correlation between vitamin D and reduced COVID-19 severity and mortality. However findings in randomized controlled trials is still limited and there is the need for more large-scale cohort and randomized controlled trials to test this hypothesis. Based on findings of previous study vitamin D suppmelentation shows protective effect in respiratory infection. Therefore, individuals with risk of vitamin D deficiency especially in this global pandemic situation is reccomended to pay attention to their vitamin D status and if needed, to take vitamin D supplement to keep serum vitamin D at optimal level.